Larvae of five species of the winter stonefly genus Capnia (Plecoptera: Capniidae) from California, U.S.A. - Stewart, Kenneth W. (Illiesia, 2011)
Associated larvae of five Capnia species from California are comparatively described and illustrated for the first time. A provisional key is presented, based on differences in the measurements and shape of the 10th tergum of mature male larvae and the visible underlying, developing epiprocts of pharate individuals. Details of the structure of the left and right mandibles, and cercal setation, are further clarified with SEM, from the previous generic description based on a single species.
Keywords: entomologija; entomology; Plecoptera; vrbnice; stonefly; Kalifornija; Capniidae; larval descriptions; Capnia; California; larve